A systematic review and meta-analysis: Memantine augmentation in moderate to severe obsessive-compulsive disorder. (December 2019) - Modarresi, Atieh; Chaibakhsh, Samira; Koulaeinejad, Neda; Koupaei, Shahram Rafieian
Highlights: We found that 20 mg/day memantine augmentation to first-line pharmacological treatment for a period of at least 8 weeks is an effective intervention for moderate to severe OCD. Stratification by refractoriness to first line treatment (serotonin reuptake inhibitors) demonstrated significant reduction of mean Y-BOCS score in both populations with no evidence of memantine augmentation favouring either of the groups. Stratification by the target dose of memantine augmentation exhibited significant reduction of mean Y-BOCS score in both 20 and <20 mg/day populations, but a more favourable outcome was observed in the 20 mg/day group. The subgroup of OCD patients with no comorbid disorders appeared to exhibit a more favourable response to memantine augmentation than those with comorbid symptoms. Memantine was generally well tolerated and the reported adverse effects were mild and transient. Abstract: A considerable proportion of obsessive-compulsive disorder (OCD) patients receiving first-line pharmacological therapy, fail to fully respond to treatment and continue to exhibit significant symptoms. In this systematic review, we evaluate the efficacy of memantine, as a glutamate-modulating agent, in moderate to severe OCD. Single and double blinded as well as open-label trials of memantine augmentation in adults with OCD were considered. Yale-Brown Obsessive Compulsive Scale (Y-BOCS) scores were the primary outcome measure. The electronic databases of PubMed, Scopus, Embase and Google Scholar were searched for relevant trials using keywords 'obsessive-compulsive disorder OR OCD' AND 'memantine'. The meta-analysis of eight studies involving 125 OCD subjects receiving memantine augmentation exhibited a significant overall mean reduction of 11.73 points in Y-BOCS scores. The categorical analysis of treatment response (a minimum of 35% reduction in Y-BOCS) in four double-blind placebo-controlled studies indicated that OCD patients receiving memantine augmentation were 3.61 times more likely to respond to treatment than those receiving placebo. We found that 20 mg/day memantine augmentation to first-line pharmacological treatment for a period of at least 8 weeks is a safe and effective intervention for moderate to severe OCD.